THE METHOD DEVELOPMENT OF ANALYSIS Cd, Cu, Pb AND Zn IN SEA WATER BY ABSORPTIVE STRIPPING VOLTAMMETRY (ASV) IN THE PRESENCE OF CALCON AS COMPLEXING AGENT - Deswati Deswati; Hamzar Suyani; Safni Safni (Universitas Gadjah Mada, 2012)
A sensitive and selective absorptive stripping voltammetric (AdSV) method to determine Cd(II), Cu(II), Pb(II) and Zn(II) in sea water is proposed. The aim of this study was to get optimum condition for the determination of Cd(II), Cu(II), Pb(II) and Zn(II). Absorptive stripping voltammetry has been used for ultra trace determination of Cd(II), Cu(II), Pb(II) and Zn(II) using calcon as a complexing agent (ligand). In this case, the optimum conditions were reached at 0.1 M KCl supporting electrolyte, concentration of 0.5 mM calcon for Cd(II), Cu(II) 0.3 mM while 0.7 mM for Pb(II) and Zn(II), pH 6 for Cu(II) and pH 7 for Cd(II), Pb(II) and Zn(II), accumulation potential -0.5 V for Cu(II) and Pb(II) and -0.6 V for Cd(II) and Zn(II) and accumulation time 70 sec for Cd(II), 90 sec for Cu(II) and Pb (II) while 50 s for Zn(II). At the optimum condition the relative standard deviations were 7.80%, 4.25%, 8.70% and 0.86% for Cd(II), Cu(II), Pb(II) and Zn(II) respectively for eight replicates (n = 8) measurements of 10 μg/L Cd(II), Cu(II), Pb(II) and Zn(II). The method was applied for the direct determination of Cd(II), Cu(II), Pb(II) and Zn(II) in sea water around Bungus, Padang City. Concentration Cd(II), Cu(II), Pb(II) and Zn(II) in sample were 13.200 μg /L for Cd(II), 17.200 μg/L for Cu(II), 0.089 μg/L for Pb(II) and 62.000 μg/L for Zn(II) with recovery of 98.68%, 97.99%, 96.17% and 99.96% for Cd(II), Cu(II), Pb(II) and Zn(II), respectively.